Macrophage malfunction in Triptolide-induced indirect hepatotoxicity - Qin, Tingting; Hasnat, Muhammad; Zhou, Yang; Yuan, Ziqiao; Zhang, Wenzhou (Frontiers in Pharmacology, 2022)
Background and Objective: Indirect hepatotoxicity is a new type of drug-induced hepatotoxicity in which the character of a drug that may induce its occurrence and the underlying mechanism remains elusive. Previously, we proved that Triptolide (TP) induced indirect hepatotoxicity upon LPS stimulation resulting from the deficiency of cytoprotective protein of hepatocyte. However, whether immune cells participated in TP-induced indirect hepatotoxicity and the way immune cells change the liver hypersensitivity to LPS still need to be deeply investigated. In this study, we tried to explore whether and how macrophages are involved in TP-induced indirect hepatotoxicity. Method: Firstly, TP (500 μg/kg) and LPS (0.1 mg/kg) were administrated as previously reported. Serum biochemical indicators, morphological changes, hepatic macrophage markers, as well as macrophage M1/M2 markers were detected. Secondly, macrophage scavenger clodronate liposomes were injected to prove whether macrophages participated in TP-induced indirect hepatotoxicity. Also, the ability of macrophages to secrete inflammatory factors and macrophage phagocytosis were detected. Lastly, reverse docking was used to find the target of TP on macrophage and the possible target was verified in vivo and in vitro. Results: TP pretreatment increased the liver hypersensitization to LPS accompanied by the recruitment of macrophages to the liver and promoted the transformation of macrophages to M1 type. Depletion of hepatic macrophages almost completely alleviated the liver injury induced by TP/LPS. TP pretreatment increased the secretion of pro-inflammatory factors and weakened the phagocytic function of macrophages upon LPS exposure. Reverse docking results revealed that MerTK might be the real target of TP. Conclusion: TP disrupts inflammatory cytokines profile and phagocytic function of hepatic macrophages, resulting in the production of massive inflammatory factors and the accumulation of endotoxin in the liver, ultimately leading to the indirect hepatotoxicity of TP. MerTK might be the target of TP on the macrophage, while the binding of TP to MerTK should be investigated in vivo and in vitro.